2013
DOI: 10.1021/nl400644r
|View full text |Cite
|
Sign up to set email alerts
|

Control and Near-Field Detection of Surface Plasmon Interference Patterns

Abstract: The tailoring of electromagnetic near-field properties is the central task in the field of nanophotonics. In addition to 2D optics for optical nanocircuits, confined and enhanced electric fields are utilized in detection and sensing, photovoltaics, spatially localized spectroscopy (nanoimaging), as well as in nanolithography and nanomanipulation. For practical purposes, it is necessary to develop easy-to-use methods for controlling the electromagnetic near-field distribution. By imaging optical near-fields usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…For coupling optics to electronics, surface plasmon polaritons (SPPs) are ideal carriers because they propagate as electromagnetic waves along the dielectric/metal interface and yet induce collective charge oscillations in a metal123. For this reason, the use of SPPs for on-chip optical interconnects has gained interest in recent years456789101112, although they have long been applied in biosensing13141516, lithography171819, subwavelength imaging2021 and nanomanipulation2223 due to their subwavelength-scale spatial confinement and strong local field enhancement24.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For coupling optics to electronics, surface plasmon polaritons (SPPs) are ideal carriers because they propagate as electromagnetic waves along the dielectric/metal interface and yet induce collective charge oscillations in a metal123. For this reason, the use of SPPs for on-chip optical interconnects has gained interest in recent years456789101112, although they have long been applied in biosensing13141516, lithography171819, subwavelength imaging2021 and nanomanipulation2223 due to their subwavelength-scale spatial confinement and strong local field enhancement24.…”
mentioning
confidence: 99%
“…In recent years, various multiplexing methods have been proposed to increase the deliverable channel number. For instance, structures have been designed in such a way that either the directionality25 or the beam shape of the output SPPs is controlled by the polarization23, wavelength26 and intensity patterns of incident waves22. While these studies demonstrated great potential, the number of controllable transmission channels remains small mainly due to the use of periodically ordered structures.…”
mentioning
confidence: 99%
“…Plasmonic nanostructures can be coupled via their near-field when the hot spots (two adjacent) space is pronounced lower than the plasmon resonance wavelength, and this effect has garnered much interest. 1 Such as the apertureless near-field optical microscopy of single molecules, 2 the Au SP interference patterns using Scanning Near Field Optical Microscope (SNOM) optical microscope system, 3 and later, the plasmon-enhanced Raman Scattering by carbon nanotubes optically coupled with near-field cavities 4 have been investigated. All the near-field coupled investigations have in common that the fundamental SP resonance is hybridized due to interactions.…”
mentioning
confidence: 99%
“…6(a). These patterns should be detectable in the near-field measurements and have much in common with the standing waves of surface plasmon polaritons excited between a pair of thin slits cut out of a metal film which were investigated recently both experimentally and theoretically [24]. The similar field structure was also predicted to describe the plasmon-assisted two-slit Young's experiment [25].…”
Section: The Effect Of the Stripe Geometry On The Properties Of Tmentioning
confidence: 60%